Climate and Volcanic Activity Modulate Area–Distance Effects on Plant Diversity Along the Temperate–Subarctic Island Volcanic Arc - Kirill Korznikov; Vyacheslav Barkalov; Pavel Fibich; Jan Altman; Jiří Doležal (Journal of Biogeography, 2026)
Aims To evaluate how equilibrium (ETIB) and niche‐based (NTIB) island‐biogeography frameworks jointly explain taxonomic and phylogenetic diversity in a temperate–subarctic, volcanically active archipelago. Location Kuril Islands, northwestern Pacific (44°–50° N). Time Period Present. Taxon Vascular plants. Methods We compiled island‐level floras. We quantified species richness (SR) and phylogenetic diversity metrics and related them to latitude, area, distance, a composite isolation index, elevation, volcanic bedrock cover, vegetation‐type diversity and aggregated climatic indices. Analyses combined linear and second‐order polynomial regressions, β‐diversity partitioning, non‐metric multidimensional scaling and structural equation models. Results Latitude emerged as the primary large‐scale filter shaping both SR and phylogenetic diversity. Volcanic activity and isolation further constrained floristic diversity, together generating a pronounced mid‐archipelago diversity trough. Maximal elevation was associated with higher SR but did not translate into detectable shifts in phylogenetic structure. Island area influenced diversity mainly indirectly, through its links with elevation and dispersal accessibility. Floristic differences among islands were driven predominantly by species turnover rather than nested species loss, indicating systematic replacement along the latitudinal gradient. Isolation effects were strongly non‐linear, consistent with threshold‐like limits to colonisation. Main Conclusions Area–distance relationships predicted by ETIB are strongly context‐dependent. Macroclimatic filtering and long‐term volcanic activity outweigh simple spatial predictors, while habitat heterogeneity exerts a secondary, modulatory role. Together, our results integrate ETIB and NTIB perspectives by showing how environmental filtering and niche availability interact in a volcanically active, temperate–subarctic island system.